ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI TERJADINYA KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN BADAN USAHA MILIK NEGARA - LUSSY WIDIA ASMARANINGTYAS; UMI MUAWANAH (Jurnal Akademika, 2022)
This study aims to determine whether financial ratios consisting of profit margin ratios, liquidity ratios, operating efficiency ratios, profitability ratios, financial leverage ratios, cash position ratios, and growth ratios can be used as a predictor of financial distress conditions in BUMN companies, as well as to find out which financial ratios are the most dominant in predicting financial distress conditions in State-Owned Enterprises for the 2013 - 2019 period. In this study the approach used is a quantitative approach. The types of data used in this study are nominal, ordinal, interval, and ratio. That is data indirectly in the form of company financial statements. The population in this study are all BUMN Banking Sector Companies that are listed on the Indonesia Stock Exchange, as well as being a research sample, or also known as population research. as many as 4 banks, namely Bank Mandiri, Bank Negara Indonesia, Bank Rakyat Indonesia, and Bank Tabungan Negara. The results were processed by logistic regression analysis (logistic regression technique) with the help of the SPSS IBM version 23 computer program package for Windows.The results of the study show that after testing 19 financial ratios, it turns out that these ratios can be used to significantly predict the possibility of financial distress in state-owned companies in the Banking Sector that have been listed on the Indonesia Stock Exchange. While the partial or individual test (Wald test) shows that the dominant independent variable that can be used to significantly predict the possibility of financial distress is the ratio of net income to sales (X1) with a significant level of 0.006, the ratio of current assets to current liabilities ( X2) with a significant level of 0.009, the ratio of sales to total assets (X6) with a significant level of 0.004, the ratio of sales to current assets (X7) with a significant level of 0.006, the ratio of net income to total assets (X9) with a significant level of 0.012 , the ratio of current debt to total assets (X12) with a significant level of 0.014, and the ratio of cash to current liabilities (X16) with a significant level of 0.003.Keywords: Financial ratios, financial distress conditions.